시청자 공적 가치 인식이 공영방송의 필요성과 TV 수신료 지불의사에 미치는 영향 - 박종원(Jong-won Park); 김광호(Kwang-Ho Kim) (디지털콘텐츠학회논문지, 2016)
이 연구는 2013년 KBS가 국회에 제출한 TV 수신료 인상안의 여론조사를 바탕으로 시청자의 공적 가치 인식이 공영방송에 대한 필요성과 TV 수신료 지불의사에 미치는 영향을 탐색해보자 하였다. 이를 위해 KBS가 제시한 7대 주요 수행과제를 품질, 다양성, 보편성, 사회적 가치, 글로벌 가치 등 5개의 공영방송의 공적 가치로 분류하였다. 연구결과는 다음과 같다. 첫째, KBS가 제시한 공적 가치 가운데 무료 지상파 다채널방송을 통한 디지털 복지 확대를 선택한 집단이 공영방송의 필요성을 가장 높게 인식한 것으로 조사되었다. 둘째, 수신료 1,000원 인상은 72.4%, 1,500원 인상은 43.9%가 긍정한 것으로 조사되어 KBS의 1,500원 인상안은 시청자의 수신료 지불의사를 반영한 것으로 나타났다. 셋째, 조사자의 84.6%가 공영방송의 필요성을 인식하고 있으며 공영방송의 필요성은 수신료 지불의사와 상관관계가 있는 것으로 분석되었다. 이런 연구 결과는 보편성, 사회적 가치, 품질과 같은 공영방송의 공적 가치를 성실히 수행할 때 공영방송과 수신료제도의 정당성을 확보할 수 있는 가능성을 확인해 주고 있다. This paper is designed to study how public values of viewers impact on the necessity of public service broadcasters and the willingness to payment of TV license fee based on the public-opinion survey regarding raising KBS TV license fee which was submitted to the National Assembly in 2013. To investigate this influence, seven main projects presented by KBS are classified into five public values of public (service) broadcasters such as quality, diversity, universality, social value and global value. The seven key performance tasks were presented by KBS. The study results are summarized as follows. Firstly, the survey group who selected the digital welfare enlargement by free terrestrial multi-channel broadcasting among public values recognized as highest the necessity of public service broadcasting as the most highly. Secondly, regarding the question of raising license fee, 72.4 percent of respondents were in favor of 1,000 won and 43.9 percent of respondents were in favor of 1,500 won. The result of this study shows that public service broadcasting has the possibility of securing the legitimacy of license fee policy when public service broadcasters faithfully carry out the five public values as above. KCI Citation Count: 4